Pengaruh Model Pembelajaran Team Games Tournament (TGT) Tipe Lu Lu Cina Buta Terhadap Hasil Belajar Geografi Siswa Kelas X SMAN 1 Rangsang Barat Kabupaten Kepulauan Meranti Provinsi Riau - Ilhan Erdeannda; Lailatur Rahmi; Karmelia Yuanda (Teaching and Learning Journal of Mandalika (Teacher) e- ISSN 2721-9666, 2024)
This research contributes significantly to understanding the effect of TGT learning model type Lu lu China Blind with PAK-21 principles on student learning outcomes in the context of geography lessons. The quantitative research method with Quasi experimental design provides an in-depth understanding of the positive impact of the application of this learning model. The use of post-test only control group design with two groups, experimental (X1) and control (X2), provides a solid base to evaluate the effectiveness of the learning model. The results of the post-test which showed a higher average score of experimental class students (83.44) compared to the control class (72.62) indicated that the TGT learning model can improve student learning outcomes in geography subjects. The difference in mean scores worth 10.82 provides an overview of the significant advantages of using the TGT learning model in the context of geography learning. Data analysis using t-test provides a strong statistical basis to support this finding, confirming that the application of TGT learning model has a significant positive impact on students' learning outcomes at SMAN Negeri 1 Rangsang Barat. This finding can serve as a basis for recommending the use of TGT learning model of Lu lu Cina Buta type with PAK-21 principle in learning geography in various schools. The results of this study can also be a reference base for further development in designing innovative and effective learning strategies to improve student learning outcomes.